Geochemical investigations of noble metal-bearing ores: Synchrotron-based micro-analyses and microcosm bioleaching studies. (May 2021) - Brinza, Loredana; Ahmed, Imad; Cismasiu, Carmen - Madalina; Ardelean, Ioan; Breaban, Iuliana Gabriela; Doroftei, Florica; Ignatyev, Konstantin; Moisescu, Cristina; Neamtu, Mariana
Abstract: Auriferous sulphide ores often incorporate micro-fine (or invisible ) gold and silver particles in a manner making their extraction difficult. Nobel metals are lost in the tailings due to the refractory nature of these ores. Bioleaching is an environment-friendly alternative to the commonly used and toxic cyanidation protocols for gold extraction from refractory ores. In this paper, we investigate gold and silver bioleaching from porphyry and epithermal mineralisation systems, using iron-oxidizing bacteria Acidithiobacillus ferrooxidans . The invisible Au, sequestered in refractory ores, was characterised in situ by synchrotron micro X-Ray Fluorescence (SR-μ-XRF) and X-ray Absorption Spectroscopy (XAS), offering information on Au unaltered speciation at the atomistic level within the ore matrices and at a micro-scale spatial resolution. The SR-μ-XRF and XAS results showed that 10–20 μm sized elemental Au(0) nuggets are sequestered in pyrite, chalcopyrite, arsenopyrite matrices and at the interface of a mixture of pyrite and chalcopyrite. Moreover, the preliminary bioleaching experiments of the two types of ores, showed that Acidithiobacillus ferrooxidans can catalyse the dissolution of natural heterogeneous Fe-rich geo-matrices, sequestering Au and Ag and releasing particulate phases or partially solubilising them within 60 days. These results provide an understanding of noble metal sequestration and speciation within natural ores and a demonstration of the application of synchrotron-based micro-analysis in characterizing economic trace metals in major mineral structures. This work is a contribution to the ongoing efforts towards finding feasible and greener solutions of noble metal extraction protocols. Graphical abstract: Image 1 Highlights: Application of synchrotron in characterizing noble metals in mineral structures. Au sequestration, spatial distribution and unaltered speciation within natural ores. Bioleaching study using real Au ores and native, adapted iron-oxidizing bacteria. IOB bio-oxidizes geo-matrixes leaching dissolved Ag and Au within 30–60 days. Progress towards finding greener solutions of noble metals extraction technologies.